Employment Situation of Person with Disabilities: Case Study in Indonesia - Antonio Frian; Fransiska Mulyani; Hansi Joachim; Dellia Anggreni; Willy Yanto Effendi (Integrated Journal of Business and Economics (IJBE), 2019)
Equality in an employment opportunity or commonly known Equal Employment Opportunity (EEO) is still not entirely applicable to a person with disabilities. World Report on Disability record 15,3 percent of the world population is the person with disabilities at 2010. Most of the person with disabilities had not taken part in the mainstream of social activity and mostly relied on social aid, including in Indonesia, where 74,7 percent from the total of a person with disabilities are unemployed. Their living expenses and necessities mostly sustained by their own family, government, or social organization – which had caused a considerable loss for concerned parties. This research intended to discover factors that influence the low employment of a person with disabilities in Indonesia, then aim for the correlations between those factors to the acceptance of employer for a person with disabilities, as well as recommending concerned employer or organizations in supporting employment opportunities for persons with disabilities. Research methodology is done by the survey to an employee about their viewpoint towards workers with disabilities, and data processing is done by SPSS software. Results of research show that education level and design of work procedure significantly affect the low employment rate of workers with disabilities in Indonesia. Further studies and development required to elaborate proper job design for a worker with disabilities, also for developing education system for workers with disabilities.